(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
Complete dentures remain a widely used method for oral rehabilitation in patients with total tooth loss. Despite technological advances in implant dentistry, removable complete dentures continue to play a crucial role due to their accessibility and clinical versatility. The primary objectives of complete denture therapy are restoration of masticatory function, speech, facial aesthetics, and overall quality of life. The aim of this study was to evaluate the effectiveness of complete dentures in restoring functional and aesthetic parameters based on contemporary scientific literature. A narrative literature review of clinical studies published between 2005 and 2025 was conducted using international scientific databases. Parameters analyzed included chewing efficiency, phonetic adaptation, facial aesthetics, patient satisfaction, and quality-of-life indicators. The analysis demonstrates that complete dentures significantly improve mastication, speech, and facial appearance, although functional efficiency remains lower compared with natural dentition or implantsupported prostheses. Patient satisfaction largely depends on prosthetic design, occlusal balance, and psychological adaptation. Proper clinical protocols and individualized treatment planning are essential for achieving optimal rehabilitation outcomes